Career-related teacher support: A review of roles that teachers play in supporting students' career planning. Issue 1 (23rd June 2021) - Wong, Lawrence P.W.; Yuen, Mantak; Chen, Gaowei
Abstract: Preparing adolescents for transitioning from school to work has become a priority across all developed countries due to the increasingly difficult labour market conditions and changes related to technological advances. Most recently, the COVID-19 pandemic has created additional uncertainties in the world of work. This article reviews the concept of career-related teacher support (CRTS) and illustrates the different roles that school teachers can have in influencing students' career planning and decision making. The information should be beneficial to teachers, counsellors, researchers and policy-makers seeking to optimise school-based career guidance and counselling practices. Brief suggestions are also provided for future research and practice.